Intracranial hypertension secondary to psychogenic polydipsia - Gleason, Vanessa M (Medknow Publications & Media Pvt Ltd, 2012)
Psychogenic polydipsia, in its most severe form, can lead to acute water intoxication by way of extreme hyponatremia. This results in cerebral edema, mental status deterioration and can lead to life threatening intracranial hypertension if not identified and treated urgently. However, this treatment rarely involves surgical intervention. Herein, we describe a 47-year-old man who presented to our emergency department who was found down with a decline in mental status and generalized tonic clonic seizures. He was comatose with glasgow coma score of 5. His exam was notable for sluggishly reactive pupils, absence of corneal reflexes, decorticate posturing, and globally increased tone and hyper-reflexia with upgoing toes bilaterally. Lab work revealed sodium of 107 mmol/L. CT scan of the head showed global cerebral edema with sulcal effacement. A ventriculostomy was placed with an opening pressure of 35-cm H(2)O, and cerebrospinal fluid was drained to maintain normal intracranial pressure. Fluid restriction and hypertonic saline were used to carefully correct the hyponatremia. The patient improved and at day five was neurologically intact. His history later revealed schizophrenia and a predilection for drinking greater than 8 L of diet cola daily.